ANAESTHETIC MANAGEMENT OF NESIDIOBLASTOSIS IN TWO INFANTS - Yousuf, Muhammad Saad; Nazir, Mohsin; Khan, Fauzia Anis (Journal of Ayub Medical College Abbottabad, 2017)
Nesidioblastosis is the most common cause of non-transient, recurrent and persistent hypoglycaemia in neonates and infants. It is a disorder of diffuse proliferation of beta cells of the pancreas leading to hyperinsulinemia and hypoglycaemia. The main aim is to prevent the severe episodes of hypoglycaemia which can cause damage to the brain and/or mental retardation. In this case report we present two cases of nesidioblastosis and their perioperative anaesthetic course for near-total pancreatectomy. First case was a 7 months old female who had repeated episodes of convulsions since birth. Second case was a 4-month-old female child who again presented with seizures. The challenges faced in the perioperative period were the management of perioperative blood glucose levels and haemodynamic stability. Keywords: Nesidioblastosis; Hypoglycaemia; Hyperinsulinism; Infant; Anaesthesia